The Effect of Risk-Based Bank Rating on Profit Growth of Sharia National Pension Saving Bank - Rian Dani; Novi Mubyarto; Titin Agustin Nengsih (Universitas Batanghari Jambi, 2023)
The purpose of this research was to establish whether or not there is a correlation between the RBBR ratio and the increased profitability of the Sharia National Pension Savings Bank (BTPN). The data used is secondary data pulled from the Sharia National Pension Savings Bank's (BTPN) quarterly financial reports for the years 2015 through 2022. Multiple linear regression analysis in SPSS 26 is employed for the analysis. The findings indicate that the factors Financing to Deposit Ratio (FDR), Return On Assets (ROA), Return On Equity (ROE), and Net Operating Margin (NOM) all have a role in the expansion of BTPN's profit margins. Meanwhile, the profit expansion at the Sharia National Pension Savings Bank (BTPN) is unaffected by the Non-Performing Financing (NPF) and Capital Adequacy Ratio (CAR) variables. Concurrently, the factors NPF, FDR, ROA, ROE, NOM, and CAR have large impacts on earnings expansion.